Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1753-4887.2009.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Low zinc status: a new risk factor for pneumonia in the elderly?

Abstract: Zinc may be a new risk factor for pneumonia in the elderly. In this special article, we reviewed the magnitude of the problem of pneumonia (its prevalence, morbidity and mortality) in the elderly, its etiology, and the dysregulation of the immune system associated with increasing age. In addition, we presented evidence from the literature, including work we did recently, that low zinc status (commonly reported in the elderly) impairs immune function, decreases resistance to pathogens, and is associated not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 106 publications
0
98
0
7
Order By: Relevance
“…Previous findings linked zinc deficiency to immune cell dysfunction, and to increased susceptibility to airway infections (45,73). In murine polymicrobial sepsis (67), zinc deficiency produced increased inflammation similar to that evoked here by MV.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous findings linked zinc deficiency to immune cell dysfunction, and to increased susceptibility to airway infections (45,73). In murine polymicrobial sepsis (67), zinc deficiency produced increased inflammation similar to that evoked here by MV.…”
Section: Discussionmentioning
confidence: 61%
“…Zinc is an essential micronutrient (34,(40)(41)(42), and its tissue and plasma levels are influenced by dietary intake (38,42). While severe zinc deficiency is rare in the developed world, moderate zinc deficiency is widespread, concentrated in elderly populations (42)(43)(44)(45), and can be exacerbated in critically ill patients (33,(46)(47)(48)(49). We demonstrate that both genetic MT deficiency and dietary zinc deficiency potentiate lung injury in mechanically ventilated mice, consistent with an essential role for the zinc/MT system in protecting the lung from injurious stretch.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies showed that underweight and micronutrient deficiencies were associated with higher odds of respiratory infections [2325]. …”
Section: Introductionmentioning
confidence: 99%
“…Optimal daily level of zinc supplementation ranges from 30 to 85 mg [12,13,14]. Although it is not known whether dietary zinc intake affects intraprostatic zinc levels, our earlier studies on rats have indicated that oral administration of zinc significantly increases its concentration in the prostate, but its availability in this organ varies based on individual zinc preparations, which may be based on differences in absorption associated with zinc preparations [15].…”
Section: Introductionmentioning
confidence: 99%